Clearing the Path to Truth: Clearing the Plains: Disease, Politics of Starvation and the Loss of Aboriginal Life, by James Daschuk, and the narrative of Canadian history. A Commentary - Kelm, Mary-Ellen (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2015)
This paper considers how Clearing the Plains helps contextualize, through Canada’s long history of settler colonialism, the findings of the Truth and Reconciliation Commission.